2016
DOI: 10.1007/s10854-016-4572-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Mn doped ZnO: the role of synthesis route

Abstract: Structural, morphological, optical, magnetic properties and chemical state of the constituent elements of 2 at% Mn doped ZnO samples synthesized by solid state reaction and sol-gel techniques were analyzed. The role of chemical or valency state in tuning the magnetic properties has been investigated. X-ray diffractometer, scanning electron microscope, UV-visible and X-ray photoelectron spectroscopes and superconducting quantum interference device vibrating sample magnetometer (SQUID VSM) were employed for inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…Nanostructured thin films of TM:ZnO synthesized by sol‐gel technique with annealing temperature of 500 °C exhibited strong FM . However, TM:ZnO nanoparticles synthesized by sol‐gel technique and annealed at the same temperature (500 °C) did not show any FM . On the other hand, TM:ZnO nanoparticles synthesized by the solid state reaction method with annealing temperature of 500 °C showed intrinsic FM .…”
Section: Introductionmentioning
confidence: 96%
“…Nanostructured thin films of TM:ZnO synthesized by sol‐gel technique with annealing temperature of 500 °C exhibited strong FM . However, TM:ZnO nanoparticles synthesized by sol‐gel technique and annealed at the same temperature (500 °C) did not show any FM . On the other hand, TM:ZnO nanoparticles synthesized by the solid state reaction method with annealing temperature of 500 °C showed intrinsic FM .…”
Section: Introductionmentioning
confidence: 96%
“…Previous theoretical work has confirmed that the Cr doped ZnO is ferromagnetic (FM) even at room temperature , however a high Cr concentration is required. The Mn‐doped ZnO systems have been studied extensively and observed experimentally to have an FM or antiferromagnetic (AFM) coupling . The ZnO containing Fe impurity has been shown to be AFM and FM .…”
Section: Introductionmentioning
confidence: 99%
“…Further a week FM response has been reported in ZnO nanoparticles and described as d 0 ferromagnetism. 27,28 Conflicting experimental reports further indicates that magnetic ordering inside Zn 1−x Mn x O critically depends on growth methods 8,14,15,19,21 annealing temperature 4,6,10,12 and internal defect structure 4,12,16 as well. Low energy irradiation (400 keV Ar 4+ ion-beam) is helpful for creation of particular type defects in a controlled fashion into the target.…”
mentioning
confidence: 97%
“…Transition metal (here Mn) doped ZnO thin films have been extensively studied in the past two decades because of their unique and novel optical [1][2][3][4] and magnetic [5][6][7][8][9][10][11][12] properties. However, doping concentration of transition metal (TM) ions is kept small and they are commonly described as dilute magnetic semiconductors (DMS).…”
mentioning
confidence: 99%
See 1 more Smart Citation